2009
DOI: 10.1097/ico.0b013e3181a0a3e6
|View full text |Cite
|
Sign up to set email alerts
|

Donor Risk Factors for Graft Failure in the Cornea Donor Study

Abstract: Purpose To assess the relationship between donor factors and 5-year corneal graft survival in the Cornea Donor Study (CDS). Methods Donor corneas met criteria established by the Eye Bank Association of America, had an endothelial cell density of 2300–3300/mm2, and were determined to be of good to excellent quality by the eye banks. Donor corneas were assigned using a random approach and surgeons were masked to information about the donor cornea including donor age. Surgery and post-operative care were perfor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

6
45
1
2

Year Published

2011
2011
2021
2021

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 66 publications
(54 citation statements)
references
References 12 publications
6
45
1
2
Order By: Relevance
“…The same result was recently demonstrated by the Cornea Donor Study in patients with Fuchs dystrophy and pseudophakic or aphakic corneal edema. 23 In our opinion, the results from CORTES confirm the validity of the standards for donor screening, tissue processing, and evaluation of corneas suitable for keratoplasty, currently applied by the Veneto Eye Bank Foundation.…”
supporting
confidence: 77%
“…The same result was recently demonstrated by the Cornea Donor Study in patients with Fuchs dystrophy and pseudophakic or aphakic corneal edema. 23 In our opinion, the results from CORTES confirm the validity of the standards for donor screening, tissue processing, and evaluation of corneas suitable for keratoplasty, currently applied by the Veneto Eye Bank Foundation.…”
supporting
confidence: 77%
“…The Cornea Donor Study found no influence of sex on risk of PK failure at 5 years, but corneas from female donors did have higher postoperative ECD. 24,29 Whether the sex effect we observed is related to expression of the H-Y antigen, which could be a target for allograft rejection where corneas from male donors are transplanted into female recipients, is a moot point. 30 Although further analysis did not show any of the specific donor-recipient sex combinations to be significant, this observation does warrant further investigation.…”
Section: Discussionmentioning
confidence: 77%
“…A lack of effect of donor age and donor ECD on 5-year graft survival was also found in the Cornea Donor Study. [20][21][22]24 In the Table 6 for Cox regression model).…”
Section: Discussionmentioning
confidence: 99%
“…16 Recently compiled data from the Cornea Donor Study has also shown that donor characteristics, such as donor age, ABO compatibility, method of tissue retrieval, processing factors, and timing of use of the cornea, are unrelated to the risk of graft failure. [17][18][19] Early vs late allograft rejection after penetrating keratoplasty C Perera et al…”
Section: Discussionmentioning
confidence: 99%